ANALISIS INFRASTRUKTUR PARIWISATA DALAM MENDUKUNG PENGEMBANGAN DESA WISATA CANDIREJO KABUPATEN MAGELANG - Tri Risandewi (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
This research aims to identify the conditions of transport and tourism infrastructure, especially road access, analyze contributing factors, inhibitors, opportunities, and threats in the development of rural tourism related Candirejo tourism infrastructure, as well as the strategy to develop tourism village Candirejo tourism-related infrastructure. The research was conducted using descriptive analytical approach by using SWOT. It focused on the availability of tourism infrastructure, especially transport and access to existing highways as well as supporting infrastructure facilities at the Tourism Village Candirejo. Based on the results of SWOT analysis, the internal and external factors that influence the development of rural tourism Candirejo associated transport infrastructure: Strength (availability of local transport, cooperation cooperative with the travel agent, the road conditions are good), weakness (lack of public transport lines, dependence of domestic tourists on private vehicles, lack of supporting infrastructure such as signs and street lighting. While the opportunities (the development of strategic areas of national tourism, tourist information centers and the promotion of travel packages integrated, threats (competition between tourist villages and natural disasters). Internal and external factors that influence the development of rural tourism Candirejo infrastructure-related access roads: Strength (proximity of the village Candirejo with the main destination, the road condition most are already good, has no roads connecting the hamlets), weakness (no markings roads, lack of street width, the condition of roads connecting the hamlets still a macadam and dirt roads, and inadequate drainage). Meanwhile, Opportunities (support from government programs, national policies related to ADD /village fund budget, a culture of mutual cooperation (gotong royong), foreign tourist interest in environmentally sound infrastructure development ), threats (there is no cooperation between villages in the provision and maintenance as well as the potential occurrence of a natural disaster).